(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article presents the idea of ​​including children with disabilities in the general education system in Uzbekistan, implementing the issue of integrating and educating them in an integrated and inclusive way, integrating children who are not involved in the science of the integration and inclusive education strategy into general education institutions into a full-fledged special or inclusive education system, and including and educating children in educational institutions in the regions where they live due to the remoteness of the correctional educational institution from the place of residence.